2017
DOI: 10.1136/rmdopen-2017-000481
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of embedded nurse-led versus conventional physician-led follow-up in rheumatoid arthritis: a systematic review and meta-analysis

Abstract: ObjectiveTo compare the efficacy of embedded nurse-led versus conventional physician-led follow-up on disease activity in patients with rheumatoid arthritis (RA).MethodsIn a systematic literature search, we identified randomised controlled trials (RCTs) reporting on the efficacy of nurse-led follow-up on disease control in patients with RA compared with physician-led follow-up. Primary outcome was disease activity indicated by Disease Activity Score (DAS)-28. Secondary outcomes were: patient satisfaction, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…7,11,12,14 fragmentation, but also to assist patients in making feasible plans for improving their own health, 28 thus alleviating possible psychological difficulties. 7,11,12,14 fragmentation, but also to assist patients in making feasible plans for improving their own health, 28 thus alleviating possible psychological difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,11,12,14 fragmentation, but also to assist patients in making feasible plans for improving their own health, 28 thus alleviating possible psychological difficulties. 7,11,12,14 fragmentation, but also to assist patients in making feasible plans for improving their own health, 28 thus alleviating possible psychological difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 With this model, a specialised nurse is responsible for the overall coordination, management and continuity of care for a specific episode of treatment or intervention. 11 Another study reported that NLCM did significantly minimise an RA patient's daily disability as assessed using the health assessment questionnaire-disability index. 9 As a consequence, there has been increased attention to the influence of nurse-led case management (NLCM) among arthritis patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent review of seven randomized controlled trials (RCTs) (all but one based on patients with low disease activity or remission), it was shown that both disease activity and patient satisfaction improved more in the nurse‐led than the regular care groups after 2 years, although there was no difference between groups after 1 year (de Thurah, Esbensen, Roelsgaard, Frandsen, & Primdahl, ). The only previous study (Ndosi et al, ) which also included patients with moderate or high disease activity (mean DAS28 3.89 and 3.65 in nurse‐led and regular groups, respectively) showed a numerically but nonsignificantly larger improvement in the nurse‐led group, results that were in line with those of the present study.…”
Section: Discussionmentioning
confidence: 99%